Ratio of visceral‐to‐subcutaneous fat area predicts cardiovascular events in patients with type 2 diabetes. Issue 2 (14th August 2017) - Fukuda, Tatsuya; Bouchi, Ryotaro; Takeuchi, Takato; Nakano, Yujiro; Murakami, Masanori; Minami, Isao; Izumiyama, Hajime; Hashimoto, Koshi; Yoshimoto, Takanobu; Ogawa, Yoshihiro
Abstract: Aims/Introduction: To investigate whether the ratio of visceral fat area (VFA) to subcutaneous fat area (SFA; V/S ratio) could be predictive of cardiovascular disease (CVD) as compared with VFA or SFA in patients with diabetes. Materials and Methods: A total of 682 patients with type 2 diabetes (mean age 64 ± 13 years; 41% women) were enrolled. VFA (cm 2 ) and SFA (cm 2 ) were assessed by a dual bioelectrical impedance analyzer. The patients were divided into four groups according to the quartiles of the V/S ratio. The study end‐point was the first occurrence or recurrence of CVD. Results: Over a median follow up of 2.5 years, 21 patients reached the end‐point. The number of patients who reached the end‐point was increased along with the increasing of the V/S ratio quartiles. The V/S ratio was significantly associated with incident or recurrent CVD (hazard ratio [HR] 1.82, 95% CI: 1.09–3.04, P = 0.021) after adjusting for estimated glomerular filtration rate (HR 0.98, 95% CI: 0.96–1.00), brain‐type natriuretic peptide (HR 1.00, 95% CI: 1.00–1.01), use of antiplatelet agents (HR 4.26, 95% CI: 1.63–11.13), coefficient of variation of R‐R intervals (HR 0.85, 95% CI: 0.69–1.10) and glycated hemoglobin (HR 1.37, 95% CI: 1.05–1.79). The addition of the V/S ratio to age, estimated glomerular filtration rate, brain‐type natriuretic peptide, antiplatelet agents and glycated hemoglobin significantly improved classification performance for CVD using net reclassification improvement (0.60, 95% CI: 0.21–1.00) and the integrated discrimination improvement (0.02, 95% CI: 0.00–0.05). Conclusions: The V/S ratio measured by dual bioelectrical impedance analyzer is an independent predictor of CVD in patients with type 2 diabetes. Abstract : It is unknown whether the ratio of visceral fat area (VFA) to subcutaneous fat area (SFA) (V/S ratio) could be associated with cardiovascular disease (CVD) in patients with diabetes. In this retrospective observational study, V/S ratio was significantly associated with CVD. The predictive performance of V/S ratio for CVD was higher than that of VFA, SFA and BMI.